Phase-Dependent Modulation of Signal Transmission in Cortical Networks through tACS-Induced Neural Oscillations - Fehér, Kristoffer D.; Nakataki, Masahito; Morishima, Yosuke (Frontiers in Human Neuroscience, 2017)
Oscillatory neural activity is considered a basis of signal transmission in brain networks. However, the causal role of neural oscillations in regulating cortico-cortical signal transmission has so far not been directly demonstrated. To date, due to methodological limitations, studies on the online modulatory mechanisms of transcranial alternating current stimulation (tACS)-induced neural oscillations are confined to the primary motor cortex. To address the causal role of oscillatory activity in modulating cortico-cortical signal transmission, we have established a new method using concurrent tACS, transcranial magnetic stimulation (TMS), and electroencephalography (EEG). Through tACS, we introduced 6-Hz (theta) oscillatory activity in the human dorsolateral prefrontal cortex (DLPFC). During tACS, we applied single-pulse TMS over the DLPFC at different phases of tACS and assessed propagation of TMS-induced neural activity with EEG. We show that tACS-induced theta oscillations modulate the propagation of TMS-induced activity in a phase-dependent manner and that phase-dependent modulation is not simply explained by the instantaneous amplitude of tACS. The results demonstrate a phase-dependent modulatory mechanism of tACS at a cortical network level, which is consistent with a causal role of neural oscillations in regulating the efficacy of signal transmission in the brain.